Determination of Spiritual Discipline, Motivation, Protocol Services, Ethical, Communication, Noble Morals through Work towards Effectiveness in Public Relations, Protocol of the Government of Riau Islands Province - Andi, Aludin; Wibisono, Chablullah; Supardi; Suaduond, Jogie; Prasetya Nugrahae, Andika (International Journal of Psychosocial Rehabilitation, 2020)
A series of activities constitutes a protocol in a government setting and office, as the hierarchy demands that senior officials are respected and followed, within and outside office settings. A survey method was adopted for research to determine the factors that affect personnel performance. The population consisted of 151 individuals who were the guest roommates visiting the Governor’s office. Data analysis is conducted through SEM with AMOS as the platform and SPSS for descriptive analysis of the data. The results of the study show that spiritual motivation’s effect on effectiveness is not significant but positive, the effect of discipline on effectiveness is not significant but positive, the value of effectiveness’s effect on communication is significant and positive, the effect of the amount of effectiveness on ethics is significant and positive, the moral noble effect on effectiveness is significant and positive, spiritual motivation determines protocol service, communication determines protocol service, ethics determine protocol service, moral noble determines protocol service, and work effectiveness determines protocol service. It is concluded that the protocol’s demand to look diligent and alert adds to the obligation owned by the contract.